1995
DOI: 10.1093/jpepsy/20.6.753
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Deficit and Academic Performance in Children and Adolescents Following Traumatic Brain Injury

Abstract: Evaluated the utility of neuropsychological testing in predicting academic outcome in children 1 year following traumatic brain injury (TBI). Fifty-one school age children who were admitted to hospital after TBI were assessed with a battery of neuropsychological measures at 3 months postinjury. Academic achievement was assessed at 3 and 12 months postinjury. The neuropsychological battery included intelligence testing and measures of memory, learning, and speed of information processing. Academic outcome was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
63
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 0 publications
10
63
0
2
Order By: Relevance
“…These rates of clinically significant change were somewhat lower than anticipated, but may be attributable to the use of a lower cutoff score. This finding also is consistent with literature that suggests low sensitivity to the behavioral sequelae of pediatric TBI (Kinsella et al, 1995;Knights et al, 1991). In fact, two studies found that structured interviews identified more post-TBI behavior problems than parent ratings (Bloom et al, 2001;Green, Foster, Morris, Muir, & Morris, 1998).…”
Section: Summary Of the Current Worksupporting
confidence: 91%
“…These rates of clinically significant change were somewhat lower than anticipated, but may be attributable to the use of a lower cutoff score. This finding also is consistent with literature that suggests low sensitivity to the behavioral sequelae of pediatric TBI (Kinsella et al, 1995;Knights et al, 1991). In fact, two studies found that structured interviews identified more post-TBI behavior problems than parent ratings (Bloom et al, 2001;Green, Foster, Morris, Muir, & Morris, 1998).…”
Section: Summary Of the Current Worksupporting
confidence: 91%
“…Studies comparing the pattern of WRAT subtest scores disclosed that arithmetic scores were lower than either spelling or reading scores (Berger-Gross & Shackelford, 1985;Chadwick et al, 1981;Levin & Benton, 1985) or did not identify any differences in performance across subtests (Kinsella et al, 1995;Perrott et al, 1991). Berger-Gross and Shackelford (1985) noted that arithmetic scores remained lower than reading and spelling scores even if IQ scores or the duration of impaired consciousness was covaried.…”
mentioning
confidence: 99%
“…Several studies have noted high rates of academic failure and changes from regular to special educational programming after TBI. Either full special educational support or a combination of regular and special educational placement was described in 50 to 75% of samples of severely injured children and adolescents (Brink, Hale, Garrett, Woo-Sam, & Nickel, 1970;Donders, 1994;Heiskanen & Kaste, 1974;Kinsella et al, 1995Kinsella et al, , 1997Klonoff, Low, & Clark, 1977). colleagues (1995, 1997) recently reported that changing from regular to special educational programming was not related to academic achievement scores but was related to teacher ratings of school performance, indices of adaptive behavior, lower verbal memory scores, and the presence of behavior problems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Both injury severity, as measured by the Glasgow Coma Scale (GCS), and neuropsychologic performance 3 months after head injury have been shown to predict special educational needs. 24 Donders found better performance IQ in children (10 to 17 years old) having mild or moderate head injury compared with severe head injury, but verbal IQ and memory did not differ with severity. 8 Research by Kaufmann et al 23 with 7-to 16-year-olds at 6 months postinjury produced similar results for severity of injury.…”
Section: Effects On Injured Childrenmentioning
confidence: 87%